Sex differences in 6-OHDA lesioned rats in a preclinical model for Parkinson’s disease - Lima, Raquel de Souza (2025)
Although Parkinson’s disease (PD) was first described in 1817, its etiology remains unclear. The primary neurotransmitter system affected in PD is the nigrostriatal dopaminergic pathway, whose dysfunction leads to the hallmark motor symptoms of the disease. These motor symptoms typically emerge only after approximately 80 % of dopaminergic neurons are lost, complicating early detection and intervention. For this reason, it is important to know more about the stages prior to the appearance of symptoms that could represent the progression of the disease. Additionally, substantial evidence suggests sex differences in PD prevalence and progression, with men more frequently affected than women. However, most preclinical studies using animal models of PD have been conducted exclusively on males, limiting our understanding of neurochemical and behavioral differences between sexes, particularly under moderate dopaminergic lesions. To address this, we used the unilateral 6-hydroxydopamine (6-OHDA) model of PD, inducing moderate lesions in the substantia nigra pars compacta (SNpc) to investigate sex-specific variations. Our study revealed distinct neurochemical and behavioral profiles in male and female animals, including sex-specific responses to amphetamine and apomorphine challenges. These pharmacological tests highlighted contrasting patterns in asymmetric and symmetric behaviors between sexes. Moreover, we considered individual variability often overlooked in animal models, which could provide critical insights into resilience or susceptibility to dopaminergic loss. These findings underscore the importance of incorporating sex as a biological variable in PD research to better understand the disease’s underlying mechanisms and to improve strategies for early diagnosis and therapeutic intervention.